Review: What Is Gnosticism? - Edwards, Mark (The journal of theological studies, 2005)
What Is Gnosticism? Karen L. King xiv + 343 Cambridge, MA The Belknap Press of Harvard University Press 2003 0 674 01071 X £19.95